Estudo do Potencial de Produção de Néctar da Jitirana Branca (Merremia Aegyptia) em Área de Caatinga no Sertão Central em Quixeramobim-Ce - Pereira, Daniel Santiago (Universidade Federal Rural do Semi-Árido, 2008)
Néctar; entomofauna; Merremia aegyptia
Study of Potential for Production of nectar of Jitirana White (Merremia Aegyptia) in the area of Caatinga Hinterland in Central Quixeramobim-Ce
Keywords: The objective of this study was to investigate whether the different timing of collection of nectar in areas hive influencing the volume, concentration of sugar and sugar produced by all its flowers a; their floral density per sqm has averaged 33.7 flowers; presented wide range of flower visitors (hymenopteros, coleopterans, hemípteros, flies, and birds), its volume of nectar ranged from agreement with the time of collection and no replenishment of nect; Néctar; Entomofauna; Merremia aegyptia; CIENCIAS AGRARIAS::MEDICINA VETERINARIA